HUBUNGAN TINGKAT PENGETAHUAN HIPERTENSI PADA LANSIA DENGAN KEPATUHAN MENGIKUTI TATA PELAKSANAAN HIPERTENSI - Anitha, Anitha (Jurnal Nurse, 2022)
Hypertension is a condition where a person's blood pressure is above the optimal normal limit of 120 mmHg for systolic and 80 mmHg for diastolic. This disease can be categorized as a disease because the patient does not know he has hypertension before checking his blood pressure. This study aims to determine the relationship of knowledge level, hypertensive disease in elderly with elderly compliance in following posyandu elderly in Rawa Buaya Cengkareng, West Jakarta. The design of this study is descriptive correlation with cross sectional approach with a large sample of 73 respondents recruited with random sampling. Data collection using instrument in the form of kuesiner. The data analysis is univariate analysis in the form of frequency distribution and bivariate analysis in the form of different test of two proportions (chi-square). Of the 73 respondents the average age of the elderly between 60-74 years is 79.5%, the most sexes are women 67.1%, the most basic educated elderly are 49.3%, the highest level of knowledge of the elderly (high ) was 64.4%, while for a good compliance rate of 49.3%. There is no significant correlation between Knowledge with compliance in following the posyandu of mswarling elderly marsh swamp crocodile cengkarteng west jakarta. (P value = 0.688).